Analisis Yuridis Hukum Lingkungan Terhadap Banjir Kota Kendari Akibat Alih Fungsi Kawasan Perbukitan - Syafardin Jumain; Muhammad Ilham; Patria Satya Agung Wardhana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Flooding that repeatedly struck several areas of Kendari City, most recently in May 2026, indicates serious problems in environmental governance and urban spatial utilization. Floods occurred in several areas of Kendari City, including the Tunggala area, Anawai Subdistrict in Wua-Wua District, the Anduonohu and Bunggasi areas in Poasia District, as well as the Lepo-Lepo area in Baruga District, which are located around the Kali Wanggu Watershed Area (DAS). This study aims to analyze the causes of flooding from the perspective of environmental law and examine the responsibility of local government regarding the conversion of hilly areas, the construction of subsidized housing, and the uncontrolled utilization of riverbank areas. The research method used is normative legal research with statutory and conceptual approaches. The results show that housing development and land clearing in hilly areas have reduced water catchment areas and increased surface runoff, thereby contributing to urban flooding. In addition, residential development around the Wanggu River border area has narrowed the river’s flow capacity and increased the risk of inundation during periods of high rainfall. These conditions reflect weak supervision by the local government over spatial utilization and the implementation of environmental protection instruments. From the perspective of environmental law, such problems potentially contradict the principle of sustainable development as regulated in Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 26 of 2007 concerning Spatial Planning. Therefore, stronger supervision, evaluation of development permits, and consistent enforcement of environmental law are necessary to prevent broader environmental degradation in Kendari City.